Evaluation of Canal Transportation and Centering Ability of RaCe and Af f-one Systems by Cone-beam Computed Tomography: An in Vitro Study - Mokhtari , Hadi; Razi , Sedigheh; Rahimi , Saeed; Haghighat , Pouya; Abedi, Atefeh; Behrouzpour , Elham (Iranian Endodontic Journal, 2024)
Introduction Rotary systems have made significant advances to improve their root canal preparation efficacy. These instruments can properly preserve the root canal anatomy and morphology. The present in vitro study aimed to compare canal transportation and centering ability of RaCe and Af f-one systems using cone-beam computed tomography. Materials and Methods: Thirty-six mandibular molars were included. The samples were randomly assigned to two groups (n=18): group 1, RaCe, and group 2, Af f-one. Canal preparation was conducted using the respective files according to the manufacturers’ instructions. The cone-beam computed tomographic scanning of the samples was performed before and after preparation. The data were analyzed by using two-way ANOVA. Results: In both the RaCe and Af f-one rotary systems, canal centrality and transportation were similar at coronal, middle, and apical cross-sections. In addition, canal transportation and centrality were identical in the RaCe and Af f-one rotary files (P<0.05). Conclusion: The two studied rotary systems did not exhibit significant differences in root canal transportation and preservation of root canal centrality in the apical, middle, and coronal thirds.